Sn@SnO2 attached on carbon spheres as additive-free electrode for high-performance pseudocapacitor. (10th August 2016) - Yang, Ying; Ren, Suzhen; Song, Xuedan; Guo, Yanan; Si, Duanhui; Jing, Hongyu; Ma, Shaobo; Hao, Ce; Ji, Min
Absract: Utilization of metal oxide/supports interface structures could generate high- performance electrochemical materials for clean energy storage and conversion. However, designing the metal oxide/supports interfaces with highly enhanced conductivity and cycle durability remains a significant challenge. Here, we demonstrate an in-situ growth technique to synthesize a Sn/SnO2 @C composite with nano-Sn species attached on surface of carbon spheres (denoted as Sn/SnO2 @C) during the carbonization of a sol-gel precursors of tin (IV) tetrachloride pentahydrate (SnCl4 ·5H2 O) and Resorcinol-Formaldehyde (Sn 4+ -RF) in N2 . We investigate the nucleation and crystal growth of Sn/SnO2 from Sn 4+ -RF precursor to Sn/SnO2 @C composite with the variation of the concentration of acid value and heat-treatment temperature. Sn/SnO2 @C-(1.0, 800) composite as supercapacitor electrode achieves a maximum specific capacitance of 906.8 F g −1 at a scan rate of 1 mV s −1 in 6 M KOH solution, and an excellent cycle durability of 2000 cycles at 5 A g −1 . The electrochemical performances demonstrate that charge storage occurs in Sn/SnO2 @C mainly due to redox reactions between the binary oxidation states: Sn↔Sn(OH)6 2− (IV) in basic electrolyte, hierarchical porosity and Sn/SnO2 @C distinct structure, which is formed in situ. The work provides new insights into the rational design of Sn@C composites electrode materials for pseudocapacitor and other electrochemical devices.